Drag reduction of Clark-Y hydrofoil by biomimetic fish scale structure under the condition of biomimetic jet - Yan, Hao; Xie, Tengzhou; Li, Jian; Fan, Jinchuan; Dai, Xinyue (Frontiers in Energy Research, 2024)
Hydrofoil, as the basic shape of the fluid blade, is widely used in fluid transport and energy conversion. However, friction resistance and pressure differential resistance are generated in the hydrofoil flow process, resulting in substantial energy consumption and negatively affecting the economy. On this basis, we propose two drag-reducing structures based on Clark-Y hydrofoil. In the design process of the jet structure, we considered the bionic jet velocity, jet angle and jet structure position as the design parameters and obtained the optimal jet structure by using Taguchi method. Finally, the two schemes (Clark-Yori and Clark-Yopt) are numerically simulated using large eddy simulation. Results show that when Ujet=1.44 m/s, θ=3° and x=18.6 mm, the jet structure can play a significant drag reduction effect. Compared with Clark-Yori, the drag coefficient of Clark-Yopt is reduced by 26.5%, and the lift drag ratio is increased by 16.4%. Compared with Clark-Yori, Clark-Yopt can reduce the wall shear stress of the leading edge of the hydrofoil, thereby diminishing the frictional resistance. Meanwhile, the jet structure can effectively balance the area of the lowpressure region on the suction side of the hydrofoil, significantly reducing the pressure differential resistance. Clark-Yopt can accelerate the vortex collapse that decreases turbulence intensity and turbulence resistance. Moreover, it can effectively block the near-wall reflux of hydrofoil and reduce the internal friction between the reflux and the main flow.